Effects of 70% Ethanol Extract of Foeniculum vulgare and Coleus amboinicus as a Potential Diarrhea Treatment Using Intestine Transit Method - Heriatmo, Nadia Larasinta; Sumarny, Ros; Pratama, Yori Chikita; Putri, Arini Amalia (Journal of Natural Product for Degenerative Diseases, 2024)
Diarrhea is a condition where the frequency of defecation increases more than three times a day. In underdeveloped nations like Indonesia, diarrhea is a sickness that frequently affects people. Diarrhea can be fatal, causing dehydration and even death if not treated properly. Using alternative treatments like fennel seeds and cumin leaves is one way to treat diarrhea. Fennel seeds and cumin leaves includes secondary tannin metabolites that are effective antidiarrheal agents. Test the antidiarrheal effect of Foeniculum vulgare ethanol extract (FVEE) and Coleus amboinicus ethanol extract (CAEE) using the intestinal transit method on mice was carried out on 9 groups, each group consisting of 5 mice: negative control, Loperamide control, Diapet® control, FVEE and CAEE at doses of 100, 200 and 400 mg/kg. To induce diarrhea through oral administration, castor oil was used in experiments. Four hours following the start of the induction, the treatment group received. They received norit an hour later, and the mice were sacrificed 20 minutes after receiving norit. The intestines were taken out of the mice after they had been dissected, starting from the rectum to the pylorus. Measured the length of the intestine overall and the portion that passed through the norit marker. Calculations were made to determine how much of the gut went by a marker compared to the entire intestine. The results of the study showed that FVEE has an antidiarrheal effect at a level of 100 mg/kg and CAEE has an antidiarrheal effect at a dose of 200 mg/kg.